KEEFEKTIVAN ACCRUAL BASIS DAN CASH BASIS DALAM MELAKUKAN PREDIKSI FUTURE CASH FLOW - Lalita Cahyarani; Ardiansyah Ardiansyah (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This study aims to prove the effectiveness of using the accrual and cash basis in predicting the future cash flow of manufacturing industry companies listed on the Indonesia Stock Exchange (IDX) in the 2018, 2019 and 2020 periods. The purposive sampling method is used in this study with the use of as many as 153 sample data from manufacturing industry companies obtained from company financial reports published on the website of the Indonesia Stock Exchange. Testing was carried out by running the SPSS version 25 software program by testing hypotheses on the independent and dependent variables that had been determined and then carrying out multiple linear regression analysis. The results show that earnings and cash flow are partially accepted, so they affect future cash flow. The results of this study show that simultaneously earnings and cash flow have a significant effect on future cash flow.